'Simple photograph' or work of art? Well-known image of Judges Falcone and Borsellino deemed insufficiently creative for protection under Article 2 of the Italian Copyright Act. (17th March 2020) - Mancinella, Matteo
Abstract: Rome Court of First Instance, 17th Civil Section specialized in enterprise matters, decision on 12 September 2019, No. 14758 The Rome Court of First Instance ruled that a well-known photograph depicting the Italian judges Falcone and Borsellino, relaxed and smiling during a conference in Palermo on 27 March 1992, does not fall within the scope of protection of Article 2 of the Italian Copyright Act because it is not characterized by sufficient creativity and because its author did not have an artistic objective in mind a priori.